Effect of Lysine to Digestible Energy Ratio on Growth Performance and Carcass Characteristics in Finishing Pigs - Cho, S. B. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
This experiment was performed to investigate the effects of lysine (Lys) to DE ratio on growth performance, and carcass characterics in finishing barrows. Ninety six cross-bred finishing barrows ((Landrace×Yorkshire) ×Duroc, average BW 58.25±0.48 kg) were assigned as a randomized complete block design by 2 energy levels and 4 Lys:DE ratios on the basis of BW to one of 8 treatments with 3 replications with 4 animals per pen. The levels of DE and Lys:DE ratio for each treatment were i) DE 3.35 Mcal/kg, 1.5 g Lys/Mcal DE, ii) DE 3.35 Mcal/kg, 1.8 g Lys/Mcal DE, iii) DE 3.35 Mcal/kg, 2.1 g Lys/Mcal DE, iv) DE 3.35 Mcal/kg, 2.4 g Lys/Mcal DE, v) DE 3.60 Mcal/kg, 1.5 g Lys/Mcal DE, vi) DE 3.60 Mcal/kg, 1.8 g Lys/Mcal DE, vii) DE 3.60 Mcal/kg, 2.1 g Lys/Mcal DE, viii) DE 3.60 Mcal/kg, 2.4 g Lys/Mcal DE. During finishing period from 58 kg to 103 kg of BW, increased energy density in the diet increased (p<0.05) ADG and gain:feed ratio, but did not influence ADFI. As Lys:DE ratio was increased, ADG, ADFI and gain:feed ratio were improved in finishing barrows (p<0.05). There were positive interactions (p<0.05) between carcass weight, grade, and backfat thickness and energy density and Lys level (p<0.05). In conclusion, data from our current study suggest that maximum yields including ADG, gain:feed ratio, carcass weight and grade can be achieved by administrating finishing pigs with an ideal Lys:DE ratio, Lys 2.1 g/DE Mcal.